Profil Darah dan Nilai Hematologi Domba Lokal yang Dipelihara di Hutan Pendidikan Gunung Walat Sukabumi - D.A. Astuti; D.R. Ekastuti; Y. Sugiarti; Marwah Marwah (Agricultural Faculty, 2008)
Blood profil and hematological status of local sheep under the gunung walat education forest area SukabumiABSTRACT. Gunung Walat Education Forest (HPGW) is one of special forest which integrated with farm system (Agrosilvopastural). This forest is heterogeneous which dominated with agathis, damar and pinus trees. To support the farming system is needed basic data haematology and blood profil of sheep that lived in HPGW. This research was aimed to evaluate haematological values covering Red Blood Cell, haemoglobin, Packed Cell Volume, MCV, MCH, MCHC and blood nutrient profil of lambs and ewes fed with mixed grass which is grow surrounding HPGW. Evaluation were done on 5 productive ewes and 5 male lambs 5-6 month ages, before and after eating time. The result showed that RBC of the lamb was (7.57 0.40) x 106/mm3 and for ewes was (5.71 0.05) x 106/mm3. Hb of lamb was (7.21 0.27) g/100ml and for ewes was (6.62 0.54) g/100ml, PCV of lamb was (28.10 7.21) % and ewes was (26.80 3.42) %, MCV of lamb was (32.68 1,23) fl and ewes was (50.91 1.53) fl, MCH of lamb was (10.82 0.47) pg and ewes was (12.93 0.29) pg, MCHC of lamb was (27,53 4.70)% and for ewes was (25.54 1.57) %. There were no significant difference on haematological values before and after feeding time except for Packed Cell Volume (P 0.05). The clinical result showed that lambs was suffering normocytic hypochromic anaemia and adults was suffering macrocytic hypochromic anaemia. Glucose level and total blood protein were at normal level while blood triglyseride concentration was lower than normal ewes concentration.